Providing objective feedback in supervision in motivational interviewing: results from a randomized controlled trial. Issue 4 (5th July 2020) - Beckman, Maria; Forsberg, Lars; Lindqvist, Helena; Ghaderi, Ata
Abstract: Background: The effects of the use of objective feedback in supervision on the supervisory relationship and skill acquisition is unknown. Aims: The objective of this study was to evaluate the effects of two different types of objective feedback provided during supervision in motivational interviewing (MI) on: (a) the supervisory relationship, including potential feelings of discomfort/distress, provoked by the supervision sessions, and (b) the supervisees' skill acquisition. Method: Data were obtained from a MI dissemination study conducted in five county councils across five county councils across Sweden. All 98 practitioners recorded sessions with standardized clients and were randomized to either systematic feedback based on only the behavioral component of a feedback protocol, or systematic feedback based on the entire protocol. Results: The two different ways to provide objective feedback did not negatively affect the supervisory relationship, or provoke discomfort/distress among the supervisees, and the group that received the behavioural component of the feedback protocol performed better on only two of the seven skill measures. Conclusions: Objective feedback does not seem to negatively affect either the supervisor–supervisee working alliance or the supervisees' supervision experience. The observed differences in MI skill acquisition were small, and constructive replications are needed to ascertain the mode and complexity of feedback that optimizes practitioners' learning, while minimizing the sense of discomfort and distress.